2019
DOI: 10.1039/c9cy01145e
|View full text |Cite
|
Sign up to set email alerts
|

Porous PtPd alloy nanotubes: towards high performance electrocatalysts with low Pt-loading

Abstract: Porous PtPd alloy nanotubes with Pt contents down to 5 at% are powerful, Pt-lean electrocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The processing of SPE-coated AAO thin films on glass substrate is shown in Scheme 1, following the procedure presented in previous works (Berger and Es-Souni 2016;Laghrissi and Es-Souni 2019;Es-Souni et al 2019). A 500 nm aluminum film was deposited on a heterostructure Scheme 1 Schematic representation of the fabrication procedure of SPE-coated AAO thin films on glass substrate of Au(6 nm)/Ti(4 nm)/glass using electron beam evaporation in a PVD device (PVD75, Lesker, USA).…”
Section: Spe-coated Aao Thin Films Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…The processing of SPE-coated AAO thin films on glass substrate is shown in Scheme 1, following the procedure presented in previous works (Berger and Es-Souni 2016;Laghrissi and Es-Souni 2019;Es-Souni et al 2019). A 500 nm aluminum film was deposited on a heterostructure Scheme 1 Schematic representation of the fabrication procedure of SPE-coated AAO thin films on glass substrate of Au(6 nm)/Ti(4 nm)/glass using electron beam evaporation in a PVD device (PVD75, Lesker, USA).…”
Section: Spe-coated Aao Thin Films Preparationmentioning
confidence: 99%
“…For the coating, a photo-grafting process following the procedure described in earlier work (Es-Souni et al 2019) was conducted to fill the pores with a zwitterionic polymer, Poly (sulfobetaine methacrylate), N,N-dimethyl-N-(2-methacryloyloxyethyl-N-(3-sulfopropyl)ammonium betaine (SPE).…”
Section: Spe-coated Aao Thin Films Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that incorporating a second metal into Pd nanostructures, giving rise to bimetallic nanoparticles (NPs) such as AuPd, PdNi, PdAg, can signicantly improve catalytic activity due to a synergetic effect between two combined metals. [7][8][9][10][11][12] Among these bimetallic nanoparticles, AuPd NPs are of special interest because of their high catalytic activity. [13][14][15] Currently, there are a number of synthetic procedures towards Pd-based bimetallic NPs such as co-reduction, seedmediated-growth in aqueous solution, electrodeposition, thermal decomposition, and galvanic replacement reaction.…”
Section: Introductionmentioning
confidence: 99%